The low rate of methicillin-resistant Staphylococcus aureus in Turkish children - (:unkn) unknown (NATL INST INFECTIOUS DISEASES, 2006)
During a 6-month period, swab samples were obtained from the nares, axilla, and perineum of 1,000 children, age 0 to 16 years, who were attending a pediatric outpatient clinic. Staphylococcus aureus was isolated in 173 of the children. Only one child, a 35-day-old boy who had remained at the neonatal intensive care unit for 1 week after birth, was identified as a carrier of methicillin-resistant S. aureus. Except in diagnosed cases of allergic rhinitis, potential predisposing factors for colonization with S. aureus in our sample were comparable to those in non-colonized children.
Keywords: NASAL CARRIAGE; PREVALENCE; COMMUNITY